2016
DOI: 10.3389/fneur.2016.00115
|View full text |Cite
|
Sign up to set email alerts
|

An Abbreviated Diagnostic Maneuver for Posterior Benign Positional Paroxysmal Vertigo

Abstract: IntroductionBenign paroxysmal positional vertigo (BPPV) secondary to canalolithiasis of the posterior semicircular canal is perhaps the most frequent cause of vertigo and dizziness. One of its properties is a high response rate to canalith repositioning maneuvers. However, delays in the diagnosis and treatment of this entity can range from days to years, depending on the setting. Here, we present an abbreviated variation of the Dix–Hallpike maneuver, which can be used to diagnose this disease. It is similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…In addition, some authors have added a 45 tilt of the head to explore the PSC and ASC canals, achieving a major sensitivity of BLT in the diagnosis of vertical canal BPPV. 13,14 Nevertheless, the clinical use of the BLT for the vertical semicircular canals is still controversial due to the variable proportion of patients who show vertical nystagmus in the bowing or leaning position. It has been demonstrated that the vertical head movement produced during the BLT enables the free-floating otoconia to move along the affected PSC 13 ; however, the rate of patients with a positive BLT in PSC-BPPV ranges from 20 to 75.2% of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some authors have added a 45 tilt of the head to explore the PSC and ASC canals, achieving a major sensitivity of BLT in the diagnosis of vertical canal BPPV. 13,14 Nevertheless, the clinical use of the BLT for the vertical semicircular canals is still controversial due to the variable proportion of patients who show vertical nystagmus in the bowing or leaning position. It has been demonstrated that the vertical head movement produced during the BLT enables the free-floating otoconia to move along the affected PSC 13 ; however, the rate of patients with a positive BLT in PSC-BPPV ranges from 20 to 75.2% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, many patients have difficulties bending their heads backward, especially the elderly, so the population's age is a key factor, which can explain such differences between studies. This can be avoided by applying an inclination to the patient's trunk, but it may also be difficult in some patients 14 …”
Section: Discussionmentioning
confidence: 99%
“…y, ¿puede realizarse un examen por medios virtuales que puedan ayudar al paciente? Si el interrogatorio del paciente es compatible con un síndrome vestibular episódico con desencadenantes, y estos últimos son los cambios de posición de la cabeza o cuerpo del paciente, y si el abecedario vestibuloespinal es normal, la situación más frecuente, se le puede realizar al paciente una mini Dix-Hallpike (Figura 3) [19] con una razonable sensibilidad y especificidad, para VPPB del canal posterior, el cual es la forma más frecuente de presentación [20] si el paciente refiere síntomas unilaterales, en caso de ser positiva se puede: a) tranquilizar al paciente, o b) sugerir una maniobra autoadministrada [21], o c) citarlo en la consulta o la sala de guardia para hacer una maniobra.…”
Section: Métodounclassified
“…Since its introduction, the Dix-Hallpike maneuver remains the gold-standard positioning maneuver for diagnosing PC-BPPV. However, there have been attempts to develop alternative maneuvers to the Dix-Hallpike maneuver or to modify the original Dix-Hallpike maneuver with the aim of making it easier to apply, including the side-lying test, 11 a chair-based version of the Dix-Hallpike maneuver, 12 and placing a pillow under the shoulders during the Dix-Hallpike maneuver. 13 These attempts have expanded the applicability of the positioning maneuvers for diagnosing PC-BPPV, especially in restricted clinical circumstances or in patients with limitations in neck motion or difficulty relaxing their neck.…”
Section: Introductionmentioning
confidence: 99%